Active Disturbance Rejection Control of Horizontal-Axis Wind Turbines (2017)
Abstract. Wind turbines are complex nonlinear machines whose main objective is to convert the wind energy into electric power. These systems work in two main operating regions. In region 2, the energy captured must be maximized by forcing the turbine speed to proportionally track the wind speed; in region 3, the wind speed is too high and the energy captured must be dissipated and the turbine speed must be regulated to its nominal value. Wind turbines are systems with enormous challenges, not only because of the regulation of speed and power under highly nonlinear aerodynamics, but also due to the high efficiency required even when model uncertainties, periodic disturbances, flexible modes, or system faults are present. This dissertation addresses the control of horizontal-axis wind turbines operating in regions 2 and 3 under the active disturbance rejection control paradigm. New control schemes based on the active disturbance rejection philosophy are proposed in order to tackle three specific problems in wind turbine control, such as: a) wind energy capture maximization of wind turbines operating in region 2, b) regulation of speed and power of wind turbines operating in region 3, and c) reduction of periodic loads on the rotor and the structure of the wind turbine. The proposed schemes are validated using a 5 MW reference nonlinear large-scale wind turbine implemented in the FAST (fatigue, aerodynamics, structures and turbulence) code and tested under realistic 3-D wind speed field. The FAST code is considered as a standard wind turbine dynamic simulation tool in industry. The results showed that the proposed active disturbance rejection control schemes are effective for controlling the wind turbine in regions 2 and 3, with effective attenuation of the periodic load components of the blades.